tg20°*tg40°*tg60°*tg80°=
=tg20°*(tg60-20°)*tg60°*tg(60°+20°)=
= [tg20°*tg(60°-20°)tg(60°+20°)]*tg60°=
=[tg20°*((sin60°-20°)*sin(60°+20°)/(cos(60°-20°)cos(60°+20°))]*√3 =
=[tg20°*(√3/2 *cos20° -1/2 * sin20°)(√3/2 *cos20° +1/2 * sin20°) :
(1/2*cos20°+√3/2 *sin20°)(1/2*cos20°-√3/2 *sin20°)]*√3 =
=[tg20°*(3/4*cos²20°-1/4sin²20°)/(1/4*cos20°-3/4sin20°)]*√3 =
=[(sin20°/cos20°)*(3cos²20°-sin²20°)/(cos²20°-3sin²20°)]*√3=
=[(3cos²20°*sin20°-sin³20°)/(cos³20°-3sin²20°cos20°)]*√3=
=(sin3*20°)/cos(3*20°)*√3= (sin60°)/(cos60°)*√3 = tg60°*√3 =√3*√3=3
tg20°*tg40°*tg60°*tg80°=
=tg20°*(tg60-20°)*tg60°*tg(60°+20°)=
= [tg20°*tg(60°-20°)tg(60°+20°)]*tg60°=
=[tg20°*((sin60°-20°)*sin(60°+20°)/(cos(60°-20°)cos(60°+20°))]*√3 =
=[tg20°*(√3/2 *cos20° -1/2 * sin20°)(√3/2 *cos20° +1/2 * sin20°) :
(1/2*cos20°+√3/2 *sin20°)(1/2*cos20°-√3/2 *sin20°)]*√3 =
=[tg20°*(3/4*cos²20°-1/4sin²20°)/(1/4*cos20°-3/4sin20°)]*√3 =
=[(sin20°/cos20°)*(3cos²20°-sin²20°)/(cos²20°-3sin²20°)]*√3=
=[(3cos²20°*sin20°-sin³20°)/(cos³20°-3sin²20°cos20°)]*√3=
=(sin3*20°)/cos(3*20°)*√3= (sin60°)/(cos60°)*√3 = tg60°*√3 =√3*√3=3
1) а) у^7*у^4/у^4=у^7
2) 15а^3-3а^2 b=3a^2(5a-b)
y^3-49y=y(y2-49)=y(y-7)(y+7)
xy+3y+Xz+3z=3(y+z)+x(y+z)=(3+x)(y+z)
3)6(2x+0,5)=8x-(3x+4)
12x+3=8x-3x-4
7x=-7
x=-1